Unusual crystallographic existence of a hydrated zinc(ii) bisulphate complex: Experimental and theoretical observations - Yadav, H.R.; Choudhury, A.R. (Royal Society of Chemistry, 2015)
A unprecedented hydrated zinc(ii) bisulphate complex, [Zn(H2O)6](HSO4·H2O)2 (1) has been synthesized along with a molecular ion salt, [4,4′-bipy-H+][NCS-] (2) (4,4′-bipy = 4,4′-bipyridine) and characterized by different spectroscopic tools including a single crystal X-ray diffraction study. From the X-ray crystal structure of 1, it is revealed that the Zn(ii) ion is in a perfect octahedral geometry with a ZnO6 core and the molecule crystallizes in the P21/c space group. Self-assembly of the bisulphate anions with lattice water molecules pack to form a 12-membered cyclic cluster through strong intermolecular H-bonding (O-H⋯O-S). Again four cyclic tetramers interact with one another via H⋯O bonding to form a 20-membered macrocyclic bisulphate-water cluster and extends as a 2D network along the a axis. It presents a new mode of association of water molecules with bisulphate molecules. Density Function Theory (DFT) studies agree well with the experimental findings
Only IISERM authors are available in the record.
Keywords: hydrated zinc(ii); bisulphate complex; [Zn(H2O)6](HSO4·H2O)2 (1)